Factors Affecting the Innovative Organization in the Context of Metropolitan Waterworks Authority - Tanthiew, Pichchabha; Khongmalai, Orapan (Suan Dusit Graduate School Academic Journal, 2022)
The objective of this research was to identify the factors affecting being an innovative organization and innovative process of the Metropolitan Waterworks Authority. This research was quantitative research. This research compiled the factors involved in the innovation organization from the relevant literature and theory reviews. Then, the factors obtained from the interview with experts were put into questionnaires. All questions were tested in terms of the content validity (IOC) which were between 0.500-1.000 and the reliability of the questionnaire with the coefficient of Cronbach's Alpha of 0.982 The questionnaires were collected both online and offline with the sample group of employees of the Metropolitan Waterworks Authority. The samples were recruited by using the stratified sampling by dividing the population into lines of work and randomizing the number of samples according to the proportion of the population size. The 376 completed questionnaires were obtained and the descriptive and inferential statistics were used for studying the relationships between variables. The analysis results of Structural Equation Modeling indicated that Innovation Process directly affected Organizational Performance at 62.60% (R2 = 0.626) and directly affected the Organizational Innovativeness at 53.40% (R2 = 0.534) In addition, the factors of Organizational Characteristics indirectly affect Organizational Performance and Organizational Innovativeness through the Innovation Process at 73.80% (R2 = 0.738). Then, the researcher led the results to discuss with the experts. The experts agreed with the research results and proposed a guideline for promoting and developing innovative processes in the organization by using the research results to develop the organization to become an innovative organization.